How to make sense of enabling vs. coercive formalization? - Leinonen, Tuomas (My University, 2019)
A high degree of management control and innovation have traditionally been regarded as incompat-ible. Yet, the possibility of creating such a combination continues to allure organizations and, in-deed, some have succeeded in the very task many organizational theorists deemed impossible. (See Davila et al. 2009; Pfister & Lukka 2019.) Some argue that enabling formalization (Adler & Borys 1996) plays a significant role in this so-called control and innovation dilemma (Adler & Chen 2011). However, the ultimate meaning of the seminal work of Adler and Borys (1996) has remained vague and has led to a multitude of different interpretations (see Hoy & Sweetland 2000; Chapman & Kihn 2009; Henttu-Aho 2016; Ståhlberg 2018; Janka 2019). Employing conceptual analysis, this thesis strives to clarify the concept of enabling and coercive formalization, its terminology and analyze its theoretical and conceptual foundations, suitability and applicability in the context of management control and the control and innovation dilemma. The thesis follows, to the extent necessary, the methodological guidelines and framework developed by Puusa (2008). In order to provide a framework for comparing the concept of enabling and coercive formalization with the established knowledge in management accounting, the typology of four man-agement controls by Merchant and Van der Stede (2007) was utilized. It is concluded that enabling formalization has much potential in solving the dilemma, but the theo-retical constituents of enabling and coercive formalization should be revised. It became apparent that enabling and coercive formalization could not be constrained to any single control type while also reliably maintaining all of the intended benefits. Instead, the concept seems to correlate more strongly with complete management control systems. Furthermore, the use of the term ‘formaliza-tion’ in the context of highly informal and indirect management controls was found to be theoreti-cally and conceptually problematic. In order to resolve these issues and to improve conceptual clari-ty, this research recommends that the concept should be subdivided into social and behavioral as-pects and technical and design aspects, which relate to either the organization’s culture or formaliza-tion. In this revised framework (see p. 59, 61), the more formal and direct controls relate to enabling and coercive formalization, whereas the more informal and indirect controls relate to a culture of enablement, or alternatively to a culture of coercion, and the two components together – the formal and the informal – form either an enabling or a coercive bureaucracy.

Muodollista johdon ohjausta ja innovaatiota on perinteisesti pidetty yhteen sopimattomina. Liian muodollinen ohjaus tukahduttaa innovatiivisuutta, kun taas liian löyhä ohjaus voi johtaa resurssien väärinkäyttöön ja tehokkuusongelmiin. (Davila et al. 2009.) Tähän niin kutsuttuun kontrollin ja innovaation dilemmaan on etsitty ratkaisua Adlerin ja Borysin (1996) tunnetusta mahdollistavan ja pakottavan formalisaation jaottelusta (Adler & Chen 2011). Potentiaalistaan huolimatta kyseistä artikkelia pidetään kuitenkin hyvin vaikeaselkoisena, ja tuloksena onkin syntynyt useita toisistaan eroavia tulkintoja (ks. Hoy & Sweetland 2000; Chapman & Kihn 2009; Henttu-Aho 2016; Ståhlberg 2018; Janka 2019). Tämä tutkielma on käsiteanalyysi, jonka tarkoituksena on selkeyttää Adlerin ja Borysin (1996) mahdollistavan ja pakottavan formalisaation käsitejaottelun terminologiaa sekä analysoida sen potentiaalia ja yhteensopivuutta johdon ohjausjärjestelmien ja kontrollin ja innovaation dilemman kanssa. Tutkielma hyödyntää pääsääntöisesti Puusan (2008) kehittelemää metodologista viitekehystä. Selkeämmän rakenteen luomiseksi tutkielmassa on päädytty hyödyntämään Merchantin ja Van der Stede (2007) neljän ohjaustyypin jaottelua. Tutkielman tulosten perusteella voidaan todeta, että mahdollistavalla formalisaatiolla on potentiaalia kontrollin ja innovaation dilemman ratkaisemiseksi, mutta Adlerin ja Borysin (1996) käsitejaottelua ja terminologiaa tulisi kehittää ja selkeyttää. Tutkielman tuloksista voidaan päätellä, että mahdollistavaa ja pakottavaa formalisaatiota ei voida selkeästi jaotella yksittäisiksi ohjaustyypeiksi, vaan ne muodostuvat eri ohjaustyyppien yhteisvaikutuksesta. Lisäksi termin ’formalisaatio’ käyttö kuvailtaessa hyvinkin epäsuoria ja epämuodollisia ohjaustyyppejä osoittautui ongelmalliseksi. Käsitteiden selkeyden parantamiseksi tutkielma päätyy suosittelemaan mahdollistavan ja pakottavan formalisaation käsitejaottelun osittamista sosiaalisiin ja kulttuurillisiin sekä teknisiin ja rakenteellisiin näkökulmiin, jotka puolestaan viittaavat enemmän joko organisaation kulttuuriin tai muodollisuuteen. Uudessa viitekehyksessä (ks. s. 59, 61) suoremmat ja muodollisemmat ohjaustyypit on luokiteltu mahdollistavaksi tai pakottavaksi formalisaatioksi, kun taas epäsuoremmat ja epämuodollisemmat ohjaustyypit on luokiteltu mahdollistavaksi tai pakottavaksi kulttuuriksi. Kulttuuri ja formalisaatio yhdessä muodostavat joko mahdollistavan tai pakottavan byrokratian.
Keywords: enabling, coercive, formalization, management control, innovation, mahdollistava, pakottava, formalisaatio, johdon ohjaus, innovaatio